Pevonedistat Suppresses Pancreatic Cancer Growth via Inactivation of the Neddylation Pathway - Xu, Junfeng; Li, Zheng; Zhuo, Qifeng; Ye, Zeng; Fan, Guixiong; Gao, Heli; Ji, Shunrong; Yu, Xianjun; Xu, Xiaowu; Liu, Wensheng; Xu, Wenyan (Frontiers in Oncology, 2022)
Background The neddylation pathway is aberrantly overactivated in multiple human cancers and has been indicated as an effective target for anticancer therapy in clinical trials. We aimed to study whether the neddylation pathway is upregulated in pancreatic cancer and whether pevonedistat, a first-in-class anticancer agent specifically targeting this pathway, will suppress cancer tumorigenesis and progression. Methods We evaluated the expression pattern of neddylation pathway components in 179 pancreatic adenocarcinomas (PAAD) compared to 171 normal tissues from the TCGA dataset and further assessed PAAD patient prognosis with high neddylation pathway expression via GEPIA. We then analyzed malignant cancer phenotypes both in vitro and in vivo, as well as intrinsic molecular mechanisms upon pevonedistat treatment. Results We found that the neddylation pathway was hyperactivated in pancreatic cancer. Patients with high neddylation pathway expression exhibited worse prognoses. Pevonedistat significantly inhibited the cancer cell cycle, cell growth and proliferation, increased cell apoptosis, and decreased cancer cell xenografts in a mouse model. Mechanistically, pevonedistat treatment and the siRNA knockdown neddylation pathway were able to remarkably induce the accumulation of Wee1, p27, and p21. Further mechanistic studies revealed that pevonedistat mainly impaired the ubiquitination level and delayed the protein degradation of Wee1, p27, and p21. Conclusions Our results showed that pevonedistat targeted the overexpression of the neddylation pathway in pancreatic cancer to induce cell growth suppression by inducing the accumulation of the cell cycle regulators Wee1, p27, and p21, which provides sound evidence for clinical trial of pevonedistat for pancreatic cancer therapy.